Advances in computers, volume 56 - Zelkowitz, Marvin V., 1945- (London : Academic Press, 2002)
Advances in Computers remains at the forefront in presenting the new developments in the ever-changing field of information technology. Since 1960, Advances in Computers has chronicled the constantly shifting theories and methods of this technology that greatly shape our lives today. Volume 56 presents eight chapters that describe how the software, hardware and applications of computers are changing the use of computers during the early part of the 21st century: Software Evolution and the Staged Model of the Software Lifecycle Embedded Software Empirical Studies of Quality Models in Object-Oriented Systems Software Fault Prevention by Language Choice Quantum computing and communication Exception Handling Breaking the Robustness Barrier: Recent Progress on the Design of Robust Multimodal Systems Using Data Mining to Discover the Preferences of Computer Criminals As the longest-running continuous serial on computers, Advances in Computers presents technologies that will affect the industry in the years to come, covering hot topics from fundamentals to applications. Additionally, readers benefit from contributions of both academic and industry professionals of the highest caliber. Volume 56 presents eight chapters that describe how the software, hardware and applications of computers are changing the use of computers during the early part of the 21st century: Software Evolution and the Staged Model of the Software Lifecycle Embedded Software Empirical Studies of Quality Models in Object-Oriented Systems Software Fault Prevention by Language Choice Quantum computing and communication Exception Handling Breaking the Robustness Barrier: Recent Progress on the Design of Robust Multimodal Systems Using Data Mining to Discover the Preferences of Computer Criminals.
Keywords: Computer science; Electronic books